Juvenile risk and needs assessment theory, research, policy, and practice - Sullivan, Christopher J.; Childs, Kristina K. (New York, NY Routledge, 2022)
"This book takes a comprehensive, analytic approach to understanding Juvenile Risk and Needs Assessment (JRNA), covering elements relevant to how the practice affects youths' cases and the juvenile justice system. The work draws on both analysis of the extensive research on risk and needs assessment in the juvenile justice system as well as data from the authors' recent work in the area. Authors Sullivan and Childs have extensive experience in teaching about and doing research on the juvenile justice system, including multiple studies on juvenile risk and needs assessment tools and their implementation. This expansive, integrative book leaves readers with a realistic sense of "where things stand" on the theory, research, policy, and practice of JRNA. By bringing together existing ideas and assessing them in depth, it identifies possible future paths and sparks ideas for improving the juvenile justice response to delinquent and at-risk youths. This monograph is essential reading for scholars of juvenile justice system impact and reform as well as practitioners engaged in youth and juvenile justice work ranging from the preventive to the rehabilitative stages"--
Includes bibliographical references and index.
Keywords: Juvenile courts; Juvenile justice, Administration of; Juvenile delinquency -- Prevention